Cinematographic observations of growth cycles of Chlamydia trachomatis in primary cultures of human amniotic cells. - Neeper, I D (1990)
Time-lapse cinematography was used to study the growth cycle of Chlamydia trachomatis in primary cell cultures of human amnion. Twelve preterm and twelve term placentas were obtained within 8 h of delivery, and epithelial cells were dissociated from the amniotic membranes by trypsinization and grown in Rose chambers. The epithelial nature of the cultured cells was documented by morphology and by immunofluorescence staining for cytoskeletal proteins, which matched the staining of intact amnion. With regular feedings, uninfected cultures remained healthy for up to 30 days. Confluent cultures (7 to 10 days) were infected with a genital strain (E/UW-5/CX) of C. trachomatis at 10(5) infectious units per chamber. Infections were done in culture medium without cycloheximide, which is often used to induce susceptibility of the cells. Between 66 and 90% of the cells were infected. Intracytoplasmic inclusions were visible by 18 h post infection (p.i.) and grew larger as the organisms inside multiplied. By 72 h p.i., the inclusions occupied the entire cytoplasm of the host cells. Further growth of the inclusions overdistended and ruptured the host cells on days 3 to 7. Cells not infected by the original inoculum became infected on day 5 or 6 p.i. by the chlamydial particles released from the ruptured cells. No amniotic cell was ever observed to survive the infection. The data presented support the hypothesis that amniotic epithelium is susceptible to infection and damage by C. trachomatis. This culture system provided detailed and dynamic observations of chlamydial infection under conditions more nearly physiologic than previously reported.